FROM DEPENDENCE TO INDEPENDENCE: UNDERSTANDING THE PROCESS OF CHILDREN LEARNING TO DRESS THEMSELVES - Rohinah; nimatulkhayati (Jurnal Profesi Keguruan, 2024)
Independence is a crucial aspect of early childhood development, encompassing the ability to perform simple tasks independently, such as dressing oneself. This study aims to understand the learning process of children dressing themselves at TK Amal Insani, Sleman, Yogyakarta, including the factors influencing its success and the challenges encountered. A descriptive qualitative research method was employed, with data collected through observation, interviews, and documentation. The findings indicate that consistent routines and teacher support significantly improved children's independence. Initially, most children struggled to dress themselves without assistance; however, with appropriate approaches, their fine motor skills, confidence, and independence improved. Challenges remained, such as parental overindulgence at home, anxiety, and lack of confidence in some children. Teachers and parents played vital roles in this success by providing positive reinforcement, attentive supervision, and collaborative efforts between school and family. This research concludes that consistent routines and teacher-parent collaboration positively impact children's independence. The findings can serve as a reference for designing strategies to support early childhood independence in educational and family settings.